Systematic Literature Review: The Presence of Microplastics in the Body and their Impact on Human Health - Sudaryanti, Lestari; Joewono, Hermanto Tri (Journal of Ecohumanism, 2025)
Background - Microplastics have been found in various environments, including water, air and food, increasing the risk of exposure to the human body. The accumulation of microplastics in the body can cause health impacts according to the route of entry into the body. Objective - This study reviews literature on microplastics that accumulate in the human body and their impact on health. Microplastics are small plastic particles that often come from consumer products and environmental pollution, and have been detected in various tissues of the human body. In the human body, microplastics cause oxidative stress conditions, affect the general body system and cause disorders in organ systems including the digestive system, respiratory system, reproductive system, trigger inflammation and potentially have long-term effects on the endocrine and nervous systems. Method - This study presents current evidence on the mechanisms of exposure, distribution of microplastics in organs, and health implications, providing important insights for the development of mitigation strategies and public health policies. The literature review articles obtained were screened with predetermined criteria. After screening, 10 main reference articles were obtained. Result - The results of this study showed that there were 10 articles stating that the presence and form of microplastics in the human body were found, and explained that there were health impacts due to exposure to microplastics on human health. The conclusion that can be drawn from this literature review is that microplastics have a long-term health impact on humans. Microplastics have additive carrier properties that can cause cancer. However, no research has been found on the real impact of microplastics that cause death. Implication - Food and beverage companies and the pharmaceutical industry should increase surveillance of microplastic contamination in their products and invest in more advanced filtration technology to protect consumers. In addition, the government and health sector need to develop mitigation policies and educate the public about the risks of microplastics and encourage innovation in reducing the use of single-use plastics.